Assessment of the psychometric properties of the 17- and 6-item Hamilton Depression Rating Scales in major depressive disorder, bipolar depression and bipolar depression with mixed features. (January 2019) - Kieslich da Silva, Alexandre; Reche, Mateus; Lima, Ana Flávia da Silva; Fleck, Marcelo Pio de Almeida; Capp, Edison; Shansis, Flávio Milman
Abstract: Assessing therapeutic response in depression requires scales that adequately measure the core symptoms of depressive symptomatology. The main goal of this study was to assess the psychometric properties of the 17-item Hamilton Depression Rating Scale (HAM-D17) and the 6-item Hamilton Depression Rating Scale (HAM-D6) in patients with Major Depressive Disorder (MDD), bipolar depression and bipolar depression with mixed features. We conducted a reanalysis of a pragmatic clinical trial in an outpatient clinic for mood disorders that included eight weeks of follow-up. A Mokken analysis was performed to evaluate the unidimensionality of the HAM-D17 and HAM-D6, and the Spearman correlation was used to assess concurrent validity between the HAM-D17, the HAM-D6 and quality of life scale (SF-36 and WHOQOL-BREF) scores. A total of 237 patients with a mean age of 40.2 years (±11.7) were included. According to the DSM-IV criteria, 58 (24.5%) were diagnosed with MDD and 73 (30.8%) were diagnosed with bipolar depression. Bipolar depression with mixed features was diagnosed in 106 (44.7%) patients according to the DSM-IV and supplemented by the Cincinnati criteria. Only the HAM-D6 scale proved to be unidimensional, showing strong homogeneity for evaluating MDD, moderate homogeneity for bipolar depression and weak homogeneity for bipolar depression with mixed features. Both the HAM-D17 and the HAM-D6 had inverse, significant correlations at baseline with SF-36 and WHOQOL-BREF scores. This is the first study to include bipolar depression patients with mixed features in an assessment of HAM-D6 unidimensionality. Highlights: The HAM-D6 proved to be a unidimensional scale. The HAM-D6 can be used to evaluate heterogeneous depression samples. The HAM-D6 can be used to evaluate bipolar depression with mixed features. Both HAM-D17 and HAM-D6 showed inverse correlation with the quality life scales. The HAM-D6 had not significant difference in effect sizes when compared with the HAM-D17.